2006
DOI: 10.1088/0031-9155/51/12/005
|View full text |Cite
|
Sign up to set email alerts
|

A new magnetic resonance electrical impedance tomography (MREIT) algorithm: the RSM-MREIT algorithm with applications to estimation of human head conductivity

Abstract: We have developed a new Magnetic Resonance Electrical Impedance Tomography (MREIT) algorithm, RSM-MREIT algorithm, for noninvasive imaging of electrical conductivity distribution using only one component of magnetic flux density. The proposed RSM-MREIT algorithm uses Response Surface Methodology (RSM) algorithm for optimizing the conductivity distribution through minimizing the errors between the measured and calculated magnetic flux density. A series of computer simulations have been conducted to assess the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 33 publications
0
57
0
Order By: Relevance
“…Some research [6,[28][29][30] showed that the realistic head model with anisotropic and inhomogeneous conductivity could improve the accuracy of the source location in EEG/MEG analysis. Presently, the MREIT algorithms [20,21] were used in human head only under the condition of the piece-wise homogeneous conductivities of the tissues. Some other MREIT algorithms were not suitable to reconstruct the conductivities of the complex head tissues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some research [6,[28][29][30] showed that the realistic head model with anisotropic and inhomogeneous conductivity could improve the accuracy of the source location in EEG/MEG analysis. Presently, the MREIT algorithms [20,21] were used in human head only under the condition of the piece-wise homogeneous conductivities of the tissues. Some other MREIT algorithms were not suitable to reconstruct the conductivities of the complex head tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid the singularity occurring when r = r ' , B(r) is treated as a node variable and J(r ' ) is used at the centre of each finite element in Eq.3. The comparison between the analytical solution and the numerical solution by FEM method was performed [20,21] to indicate the feasibility of solving the forward problem using the FEM.…”
Section: Forward Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The impedance distribution is then estimated based on the measured voltages and medium geometry. Some of typical applications of these techniques are for geophysical imaging [1,2,3], process monitoring [4,5], and functional imaging of the body [6,7].…”
Section: Introductionmentioning
confidence: 99%